(untitled) (Damascus University Journal for the economic and Political sciences, 2026)
By applying this study on Sheraton Hotel in Damascus,this study aims to evaluate syrian hotels performance by using balanced scorecard , and concrete recommendations to improve Sheratons hotel performance by knowing weakness and strengthen points. The researcher used the descriptive analytical approach to achive the aim of this study ,and she designed balanced scorecard with it four dimensions (financial dimension, Clients dimension ,internal operation dimension ,and learning and growth dimension)to find out the direction of the hotel’s overall performance The study showed the following results • Balanced scorecard operates within an integrated framework of financial and non-financial indicators those interact and integrate on the principle of main function at hotel • 2. Balanced scorecard contributes to performance evaluation and discovers mistakes to improve their performance.